Maternal geohelminth infections are associated with an increased susceptibility to geohelminth infection in children: a case-control study. - Raaj S Mehta; Alejandro Rodriguez; Martha Chico; Irene Guadalupe; Nely Broncano; Carlos Sandoval; Fernanda Tupiza; Edward Mitre; Philip J Cooper (PLoS Neglected Tropical Diseases)
Background Children of mothers infected with soil-transmitted helminths (STH) may have an increased susceptibility to STH infection. Methods and findings We did a case-control study nested in a birth cohort in Ecuador. Data from 1,004 children aged 7 months to 3 years were analyzed. Cases were defined as children with Ascaris lumbricoides and/or Trichuris trichiura, controls without. Exposure was defined as maternal infection with A. lumbricoides and/or T. trichiura, detected during the third trimester of pregnancy. The analysis was restricted to households with a documented infection to control for infection risk. Children of mothers with STH infections had a greater risk of infection compared to children of uninfected mothers (adjusted OR 2.61, 95% CI: 1.88-3.63, p<0.001). This effect was particularly strong in children of mothers with both STH infections (adjusted OR: 5.91, 95% CI: 3.55-9.81, p<0.001). Newborns of infected mothers had greater levels of plasma IL-10 than those of uninfected mothers (p=0.033), and there was evidence that cord blood IL-10 was increased among newborns who became infected later in childhood (p=0.060). Conclusion Our data suggest that maternal STH infections increase susceptibility to infection during early childhood, an effect that was associated with elevated IL-10 in cord plasma.